Numerical study on the size effect on the mixing in 2×1, 3×3 and 5×5 rod bundle subchannels - Bin Han; Yuanyuan Yin; Xiaoliang zhu; Bao-Wen Yang; Aiguo Liu; Shenghui Liu (Nuclear Engineering and Technology)
Mixing Vane Grid (MVG) is considered as one of the most important components in the fuel assembly which not only plays the role of supporting the rod bundles but also improves the Critical Heat Flux (CHF) in the reactor core. Modeling and measuring the flow behavior accurately in the rod bundle is the key to understanding and learning complex grid performance in the fuel assembly and will develop high performance MVG. Usually, the fuel assembly in the reactor core consists of 17 × 17 or 16 × 16 rod bundles, it is hardly to use the original MVGs to perform study. The representative smaller prototypical grids are applied. Different bundle sizes are used including 1 × 1, 2 × 1, 3 × 3 and 5 × 5 et al. It is an absolute question of how the smaller size rod bundles are prototypical that could fully reflect the true flow and heat transfer behavior in a reactor core. In this paper, the effect of bundle size on flow and heat transfer is investigated under sizes of 2 × 1, 3 × 3 and 5 × 5. Firstly, the boundary settings in 2 × 1 are studied and the surface averaged secondary flow and local flow at the gap with 5 × 5 results are compared. Then the 3 × 3 and 5 × 5 bundle sizes are compared under subcooled flow. The center subchannels temperature and the void fraction distributions are analyzed. The effect of non-prototypical cold walls on heat transfer is discussed. The study shows that, different bundle sizes will produce different flow phenomena in the rod bundle, the flow pattern may not be the same with the reactor core fuel assembly, the typical bundle size selection should be based on the research purpose.